2021
DOI: 10.3390/molecules26020319
|View full text |Cite
|
Sign up to set email alerts
|

Caffeoylquinic Acid Derivatives of Purple Sweet Potato as Modulators of Mitochondrial Function in Mouse Primary Hepatocytes

Abstract: Owing to their antioxidant properties, caffeoylquinic acid (CQA)-derivatives could potentially improve the impaired metabolism in hepatic cells, however, their effect on mitochondrial function has not been demonstrated yet. Here, we evaluated the impact of three CQA-derivatives extracted from purple sweet potato, namely 5-CQA, 3,4- and 4,5-diCQA, on mitochondrial activity in primary hepatocytes using an extracellular flux analyzer. Notably, an increase of maximal respiration and spare respiratory capacity were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…The dominant phenolic compounds of the Helichrysum pallasii extracts were chlorogenic acid isomers which were previously reported as potent antidiabetic agents in vitro (𝛼glucosidase; IC50: 9.1 μg/ml and α-amylase; IC50: 9.2 μg/ml) (Oboh et al, 2015) and in vivo (Jung et al, 2006;Kamalakkannan and Prince, 2006;Ong et al, 2012;Torres et al, 2021).…”
Section: Enzyme Inhibitory Abilitiesmentioning
confidence: 88%
See 1 more Smart Citation
“…The dominant phenolic compounds of the Helichrysum pallasii extracts were chlorogenic acid isomers which were previously reported as potent antidiabetic agents in vitro (𝛼glucosidase; IC50: 9.1 μg/ml and α-amylase; IC50: 9.2 μg/ml) (Oboh et al, 2015) and in vivo (Jung et al, 2006;Kamalakkannan and Prince, 2006;Ong et al, 2012;Torres et al, 2021).…”
Section: Enzyme Inhibitory Abilitiesmentioning
confidence: 88%
“…The most abundant form of chlorogenic acid in nature is 5-caffeoylquinic acid (Olthof et al, 2001). Chlorogenic acid isomers (3-caffeoylquinic, 4-caffeoylquinic, and 5caffeoylquinic acids) show many biological activities such as antibacterial, antioxidant, anticarcinogenic, hypoglycaemic, hypolipidemic, hepatoprotective, antihistamine antimutagenic, anti-obesity, antidiabetic, antiviral, anti-Alzheimer, neuroprotective (Clifford et al, 2017;Hamed et al, 2020;Matthews et al, 2020;Torres et al, 2021). Rutin is a flavonoid found in many plants, also considered a non-toxic chemical that may be useful in biomedical applications and showing biological activities such as anti-inflammatory, anticarcinogenic, antioxidant, neuroprotective, cytoprotective, vasoprotective, cardioprotective, and hepatoprotective (Ghorbani, 2017;Shahi et al, 2019).…”
Section: Figure 2 Gc-ms Profile Of Helichrysum Pallasii Leavesmentioning
confidence: 99%
“…Torres et al indicated that the caffeoylquinic acids in acetone:water:lactic acid (40:60:1) extract from purple sweet potatoes’ tuberous roots have the potential to improve impaired mitochondrial function in hepatocytes and to increase fatty acid oxidation. They demonstrated that the addition of 5-caffeoylquinic acid or 3,4-dicaffeoylquinic acid increased the maximal respiration and the reserve respiratory capability in primary hepatocytes [ 52 ]. We found that caffeoylquinic-acid-rich fractions from wormwood and silver wormwood herb acetone extracts can modulate mitochondrial function, and that the effect on mitochondria is dose-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Caffeoylquinic acid derivatives have been reported to have a strong repair effect on oxidative damage. Torres 38 reported caffeoylquinic acid derivatives inhibit oxidative stress‐induced neurotoxicity in a concentration‐dependent manner. Jho 39 reported that 3,5‐di‐ O ‐caffeoylquinic acid can reduce the oxidative damage caused by tert‐butyl hydroperoxide or paracetamol in HepG2 and reduce cell death.…”
Section: Discussionmentioning
confidence: 99%